influence of Finance on the Management of Public Senior Secondary Scbool in Abuja, FCT - Kunuosowa , Ntmno, Goodfriday; Ibrahim, Yusuf; Yusuf , Ilewuobe (International Journal of Educational Management, 2025)
This study examined influence of finance on the management of public senior secondary schools in Abuja, FCT. The study adopted descriptive research design, two research questions and hypotheses were developed; descriptive research design was used. The population was 41l1 stakeholders while the sample size of 357 was determined by research advisors sampling table (2006). The study adopted simple random sampling technique in selecting eighteen public senior secondary schools in six area councils in Abuja, FCT The instrument used for the collection of data was a self structured questionnaire titled, Influence of Finance on the Management of Public Senior Secondary Schools Questionnaire (IFMPSSSQ) and the reliability coefficient index of 0.85 was used. Data were analysed using frequency and percentage for the demographic variables. The hypotheses were tested using One Way Analysis of Variance (ANOVA) at 0.05 mean score. Findings of the study revealed that, mostof the school facilities in secondary school in FCT were not adequately provided due to poor financing and finance significantly influence instructional supervision in secondary schools in FCT It was recommended that· public secondary schools in FCT Abuja should be adequately financed in order to improve the quality and quantity of school facilities; and effective instructional supervision should be encourage in public secondary schools in FCT Abuja through adequate financing